Impact of clinical ethics support on daily practice—First‐line managers' experiences in the Euro‐MCD project. (11th July 2019) - Silén, Marit; Svantesson, Mia
Abstract: Aim: To explore first‐line managers' experiences of what Moral Case Deliberation has meant for daily practice, to describe perceptions of context influence and responsibility to manage ethically difficult situations. Background: In order to find measures to evaluate Moral Case Deliberation, the European Moral Case Deliberation Outcome instrument was developed and is now in the stage of revision. For this, there is a need of several perspectives, one of them being the managerial bird‐eye perspective. Method: Eleven first‐line managers at workplaces, participating in the European Moral Case Deliberation Outcome instrument project, were interviewed and thematic analysis was applied. Results: Managers' experiences were interpreted as enhanced ethical climate: a closer‐knit and more emotionally mature team, morally strengthened individuals, as well as ethics leaving its marks on everyday work and morally grounded actions. Despite organizational barriers, they felt inspired to continue ethics work. Conclusion and Implications: This study confirmed, but also added ethical climate aspects, such as morally grounded actions. Furthermore, adding ethical climate as a construct in the European Moral Case Deliberation Outcome instrument should be considered. First‐line managers need clear directives from their managers that ethics work needs to be prioritized for the good of both the staff and the patients.